Deletion of Nkx2-5 in trabecular myocardium reveals the developmental origins of pathological heterogeneity associated with ventricular non-compaction cardiomyopathy. - Caroline Choquet; Thi Hong Minh Nguyen; Pierre Sicard; Emeline Buttigieg; Thi Thom Tran; Frank Kober; Isabelle Varlet; Rachel Sturny; Mauro W Costa; Richard P Harvey; Catherine Nguyen; Pascal Rihet; et al. (PLoS Genetics)
Left ventricular non-compaction (LVNC) is a rare cardiomyopathy associated with a hypertrabeculated phenotype and a large spectrum of symptoms. It is still unclear whether LVNC results from a defect of ventricular trabeculae development and the mechanistic basis that underlies the varying severity of this pathology is unknown. To investigate these issues, we inactivated the cardiac transcription factor Nkx2-5 in trabecular myocardium at different stages of trabecular morphogenesis using an inducible Cx40-creERT2 allele. Conditional deletion of Nkx2-5 at embryonic stages, during trabecular formation, provokes a severe hypertrabeculated phenotype associated with subendocardial fibrosis and Purkinje fiber hypoplasia. A milder phenotype was observed after Nkx2-5 deletion at fetal stages, during trabecular compaction. A longitudinal study of cardiac function in adult Nkx2-5 conditional mutant mice demonstrates that excessive trabeculation is associated with complex ventricular conduction defects, progressively leading to strain defects, and, in 50% of mutant mice, to heart failure. Progressive impaired cardiac function correlates with conduction and strain defects independently of the degree of hypertrabeculation. Transcriptomic analysis of molecular pathways reflects myocardial remodeling with a larger number of differentially expressed genes in the severe versus mild phenotype and identifies Six1 as being upregulated in hypertrabeculated hearts. Our results provide insights into the etiology of LVNC and link its pathogenicity with compromised trabecular development including compaction defects and ventricular conduction system hypoplasia.